Experience using low doses of calcineurin inhibitors in the treatment of refractory lupus nephritis - César Augusto Restrepo Valencia; Consuelo Vélez Álvarez (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2014)
Objective: To evaluate the effectiveness of calcineurin ciclosporin and tacrolimus inhibitors to induce remission in patients with refractory lupus nephritis. Patients, materials and methods: Patients with lupus nephritis class IV-G who despite receiving the rapy with high doses of steroid and with a cytostatic (cyclophosphamide or mycophenolate) for 3 months had not been able to induce some kind of remission.The exclusion criteria were creatinine levels greater than 3 mg / dl, pregnancy, previous history of exposure to calcineurin inhibitors, cancer, active infections, uncontrolled hypertension, and negligence with medication intake. The recommended dose of cyclosporine was 3 mg / kg / day and tacrolimus 0.1 mg / kg / day, in joint with prednisone 0.3 mg / kg / day, cyclophosphamide 1 mg / kg / day or mycophenolate mofetil 1 gram every 12 hours. The cyclophosphamide was administered only during 6 months, after which it was changed to azathioprine at doses of 1 mg / kg / day. Still, mycophenolate was continued at the same dose. All patients completed a minimum period of 12 months follow-up, it was considered that patients achieved partial remission when proteinuria decreased by 50% of the baseline value or its value decreased to less than 1 gram in 24 hours, decrease of leukocytes count and red blood cells in urine of 50%, and creatinine values were stable. A complete remission was considered when there was a reduction in proteinuria in a value less than 300 mg per 24 hours, urinary sediment with less than 3 red blood cells, less than 5 leukocyte for each high power microscopic field, and a creatinine value reduction by 50% or reaching a normal value. Results: Twelve patients met the inclusion criteria and initiated the calcineurin inhibitor protocol. Two presented accelerated deterioration in their function and required chronic dialysis therapy. Ten patients with active treatment completed 12 months of followup, of which 4 (40%) had partial remission (PR), 5 (50%) complete remission (RC). One patient had no significant modification to his baseline values. The following findings were made for all the patients with any significant degree of remission: their creatinine levels were reduced significantly from an average value of 1,34 +/-0,7 mg/dl to an average of 0,96 +/- 0,3 mg/dl and 0,97 +/- 0,24 mg/dl for measurements taken 6 and 12 months respectively after the start of the treatment (p<0,05). The protein levels in the urine in a timeframe of 24 hours changed from a baseline value of 2865 +/- 2586.7 milligrams to 824 +/- 981.9 milligrams at 6 months, and 488 +/- 697.7 milligrams at 12 months (p <0.05). On average, in both PR and CR patients, the C3 levels raised unlike the values for antinuclear antibodies that were diminished. No patients died, nor were there significant side effects trigge red by medications. No patient presented relapses during the follow-up time. Conclusion: The calcineurin inhibitors at low doses are an important alternative to induce partial or complete remission in patients with refractory lupus nephritis compared to classic steroid and cytostatic treatment. It is required to do a long-term follow-up to establish its safety profile at low doses and relapse rate after suspension.